Similarities and differences between working processes of Ranque effect and Hartmann–Sprenger tube - V. I. Kuznetsov; V. V. Makarov; A. Yu. Shander (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The physical and mathematical models of the processes occurring in the vortex tubes (Ranque effect) and Hartmann–Sprenger tube. The physical models most closely corresponding to the physical processes in these devices have been identified. The similarities and differences between the effects arising during the operation of vortex tubes and the Hartmann–Sprenger tube are found. The proof of the influence of viscosity on the Ranque effect and the interaction of gases in the Hartmann–Sprenger tube is given. Regularities of changes in total pressure and total temperature in a vortex tube and a Hartmann–Sprenger tube are given. The factors influencing the energy exchange in the vortex tube and the Hartmann–Sprenger tube are determined. The influence of the exchange of work and heat on the Ranque effect and the Hartmann–Sprenger tube is revealed. The mechanism of energy transfer between gas layers in a vortex tube and in a dead-end Hartmann– Sprenger cavity is found